2015
DOI: 10.18805/lr.v0iof.7108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different processing methods on proximate, mineral and antinutrient content of lima bean (Phaseolus lunatus) seeds

Abstract: The present study was formulated to analyze the effect of common processing methods on proximate, mineral and antinutrient content of lima bean. The protein content in the present study enhanced from 24.6g in raw to 26.5g/100g on germination. The most abundant mineral in raw bean for 100g was potassium (1295.13mg), followed by calcium (326.5mg), phosphorus (153.4mg), magnesium (123.1mg), sodium (27.0mg), iron (5.43 mg). There was significant (p < 0.01) increase in calcium and phosphorus (10.81 and 14.50%) in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
4
11
0
Order By: Relevance
“…Also, the reduction in ash content may be due to the leached-out endospermic matter which contains macro and micro elements in the using water. Similar result was given by Jayalaxmi et al [12] and Farinde et al [31]. On the other hand, ash content was increased significantly in roasted seeds.…”
Section: Chemical Composition and Mineral Contents Of Lima Beansupporting
confidence: 89%
See 3 more Smart Citations
“…Also, the reduction in ash content may be due to the leached-out endospermic matter which contains macro and micro elements in the using water. Similar result was given by Jayalaxmi et al [12] and Farinde et al [31]. On the other hand, ash content was increased significantly in roasted seeds.…”
Section: Chemical Composition and Mineral Contents Of Lima Beansupporting
confidence: 89%
“…The energy value of raw lima bean was 374.47 Kcal/100g, a similar trend in our study for the effect of processing methods on carbohydrates content was observed with energy values. This suggests that cooked, soaked and dehulled lima bean could be a good ported by Jayalaxmi et al [12] and Bonita et al [7] who recorded that lima bean had high mineral content particularly of potassium, phosphors and magnesium, in comparison with cereals, the calcium and iron content were very high in it.…”
Section: Chemical Composition and Mineral Contents Of Lima Beanmentioning
confidence: 90%
See 2 more Smart Citations
“…In Green gram sprouting, roasting and pressure cooking has to be employed for 100% removal. Baddi et al (2016).…”
Section: Effect Of Processingmentioning
confidence: 99%